TAMPILAN PERTUMBUHAN F1 UMUR DELAPAN MINGGU HASIL PERSILANGAN AYAM BETINA SABU DENGAN BEBERAPA STRAIN AYAM JANTAN (F1 growth display eight weeks of age the result of crossing Sabu female chickens with several strains of roosters) - Herowati Titi Pangestuti; Herayanti P. Nastiti; Clerens W. Naetasi (JURNAL NUKLEUS PETERNAKAN, 2023)
Enhancing the productivities of domestic Sabu Island chickens can be achieved through the strategic cross-breeding of distinct chicken types. The fulfillment of local poultry demand can be augmented by implementing crosses between indigenous Sabu and Kate chickens and conventional laying hens, thereby promoting an increase in body weight gain. The primary objective of the research was to ascertain the growth performance of chickens subsequent to the crossbreeding of various lines of male and female chickens indigenous to Sabu Island. The research method used a Completely Randomized Design with three treatments (P1 = native male Sabu × native female Sabu, P2 = male Kate × female native Sabu, P3 = laying male × female native Sabu) and four replications. The material used was forty-eight chicks from crosses, each of which produced sixteen chicks. The parameters measured were feed consumption, body weight gain, and feed conversion for 8 weeks. The results of the research, Sabu, Kate, and Layer chickens showed feed consumption of 508.60 ± 87.81 gr/head/week, 372.38 ± 25.86 gr/head/week, and 1020.20 ± 53.78 gr /head/week; body weight gain 158.17 ± 36.47 gr/head/week, 115.53 ± 6.78 gr/head/week, and 272.57 ± 36.81 gr/head/week; ration conversion 3.32 ± 0.83, 3.22 ± 0.19, and 3.22 ± 36.81,. 3.77 +/- 0.30 The results of analysis of variance showed that the effect of treatment on ration consumption and body weight gain was very significant (P<0.01), but not significant on ration conversion (P>0.05). The conclusion drawn is that the growth performance of chickens exhibited an improvement through crossbreeding among various lines of male chickens and indigenous Sabu female chickens. This enhancement was particularly notable in terms of feed consumption and weight gain, as observed within the parameters of treatment P3.